2021
DOI: 10.3174/ajnr.a6894
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam CT versus Multidetector CT in Postoperative Cochlear Implant Imaging: Evaluation of Image Quality and Radiation Dose

Abstract: BACKGROUND AND PURPOSE: Cone-beam CT is being increasingly used in head and neck imaging. We compared cone-beam CT with multidetector CT to assess postoperative implant placement and delineate finer anatomic structures, image quality, and radiation dose used. MATERIALS AND METHODS:This retrospective multicenter study included 51 patients with cochlear implants and postoperative imaging via temporal bone cone-beam CT (n ¼ 32 ears) or multidetector CT (n ¼ 19 ears) between 2012 and 2017. We evaluated the visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…In agreement with several previous studies [ 13 , 16 – 18 ] and due to their superior spatial resolution and low susceptibility for metal artifacts, both FD-CT systems yield better image quality than MS-CT for evaluation of the microanatomical details of the temporal bone and the precise cochlear implant position: in our study, the HS-FD-CT with its 14-s scanning protocol provided the best visualization of the temporal bone specimens and the CI, followed closely by the FD-CT using the 20 s 70 kV and 109 kV protocol and the 9 s HS-FD-CT protocol. Although providing worst IQ among tested (HS-)FD-CT protocols, the 7 s HS-FD-CT protocol still exceeds MS-CT.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with several previous studies [ 13 , 16 – 18 ] and due to their superior spatial resolution and low susceptibility for metal artifacts, both FD-CT systems yield better image quality than MS-CT for evaluation of the microanatomical details of the temporal bone and the precise cochlear implant position: in our study, the HS-FD-CT with its 14-s scanning protocol provided the best visualization of the temporal bone specimens and the CI, followed closely by the FD-CT using the 20 s 70 kV and 109 kV protocol and the 9 s HS-FD-CT protocol. Although providing worst IQ among tested (HS-)FD-CT protocols, the 7 s HS-FD-CT protocol still exceeds MS-CT.…”
Section: Discussionsupporting
confidence: 94%
“…Because of its affordable price compared to angiography systems, lighter and smaller equipment, better spatial resolution compared to MS-CT and equal spatial resolution compared to FD-CT, the simplicity to operate and maintain, the possibility to scan seated patients and the open design to help claustrophobic patients [ 25 ], CB-CT is the preferred imaging modality for dental and maxillofacial skeleton imaging [ 25 ] and is also applicable for temporal bone imaging as well as postoperative cochlear implant control. In this context, CB-CT significantly reduces radiation dose compared to MS-CT and FD-CT [ 26 ]: for example, in a recent study, Helal et al report a median DLP of 93 mGycm for CBCT in comparison to a median DLP of 387.5 mGycm for MS-CT [ 13 ]. In this context, Burck et al measured the effective dose of CBCT in comparison to MS-CT and found an effective dose reduction of up to 97.7% via CBCT [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heute hat die DVT in vielen Zentren die CT aufgrund ihrer relativ geringeren metallischen Artefakte und Strahlenexposition ersetzt (▶ Abb. 13)[18].…”
unclassified
“…2 However, the radiation exposure in these CT-based measurements is a consideration; therefore, it is desirable to use alternate imaging methods like MR imaging to make these measurements. 10 This study aimed to test the accuracy and reliability of MR imaging-based 3D cochlear length measurements that were previously performed by CT. A secondary aim was to test the effect of the observer's experience on these measurements.…”
mentioning
confidence: 99%